How young people’s perceptions of their physical education lessons and social skills varied in terms of sociodemographic features. The case of a rural area of China - Primo, Laura; González-Hernández, Juan; Yang, Yin; Lopez de Subijana, Cristina (Frontiers in Education, 2023)
The aim of this study was to examine whether motivation, support, basic-needs satisfaction, and social skills in physical education lessons differed among Chinese secondary students from rural areas depending on their sociodemographic profiles. Two hundred and seven students enrolled in a camp organized by a non-governmental organization in Chengdu province (15.8 ± 0.8 years; 74 % female and 26 % male) completed validated Chinese versions of the pertinent questionnaires. Appropiate social skills were perceived higher by women that by men (z = 2.2; p = .014; r = .16). Inappropiate social skills (z = 2.9; p = .021; r = .22) were perceived higher among those students with lower annual home income (50,000 yuan or less). Perceived autonomy support (z = 2.9; p = .002; r = .20), basic-needs satisfaction (z = 2.9; p = .002; r = .20), and physical-education motivation (z = 4.2; p < .001; r = .30) were higher among students who practiced physical activity or sport outside school. Students who practiced during their physical-education team-sports lessons reported higher motivation for physical education (z = 2.9; p = .002; r = .20) than those who practiced individual sports. The findings from this study are relevant to practitioners who work with students from underprivileged rural areas.